Strumenti della rete e processo formativo - Giovanni, Bonaiuti (Scuole di dottorato, 2005)
The telecommunications networks offer interesting new opportunities for training. More specifically, in over ten years of studies the research tradition known as CSCL, or computer supported collaborative learning, has underscored the potential of these tools within collaborative learning dynamics. Taking its cue from a rereading of the cultural-historical stances of Vygotsky, and bringing together pedagogical reflections, the contributions of cognitive ergonomics and studies on "man-machine" interaction, this research is concerned to focus the theoretical, methodological and design elements best suited to facilitate the practices of online collaborative learning.